Inhibitor development in mild haemophilia after a major surgery for periampullary cancer (Whipple's procedure) in an elderly man. Issue 1 (29th January 2021) - Ganju, Neha; Rajendran, Jayapal; Aggarwal, Mukul; Dash, Nihar
Abstract : Around the world, with the availability of factor concentrates, patients with haemophilia have undergone major and minor surgeries. Inhibitor development in early postoperative period leading to inadequate factor recovery and ongoing bleeding is a nightmare for both operating surgeon as well as haematologists. We describe a case of an elderly man with mild haemophilia A, who was diagnosed with pancreatic carcinoma and underwent Whipple's procedure. After an uneventful procedure, he developed high-titre inhibitors and bleeding a week after surgery posing major challenges in his management. The case highlights the importance of experienced surgeons, trained haematologists, regular monitoring of factor assay/inhibitors, adequate factor and bypassing-agent support while performing such procedures.